Endometrial ablation for the treatment of heavy menstrual bleeding in obese women. Issue 1 (8th January 2013) - Madsen, Annetta M.; El‐Nashar, Sherif A.; Hopkins, Matthew R.; Khan, Zaraq; Famuyide, Abimbola O.
Abstract: Objective: To compare the efficacy and safety of endometrial ablation (EA) among obese versus non‐obese women. Methods: A retrospective cohort study of 666 women who underwent EA at the Mayo Clinic, Rochester, USA, between January 1, 1998, and December 31, 2005, was conducted. Obesity was defined as a body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters) of 30 or above. Outcome measures included treatment failure and amenorrhea. Regression models were used to compare outcomes and adjust for known confounders. Results: The mean BMI was 29.6 ± 7.7; 263 women (39.5%) were classified as obese. No difference was observed in treatment failure at 5 years between the obese and non‐obese cohorts (11.6% vs 9.7%) with an adjusted hazard ratio of 0.96 (95% confidence interval [CI], 0.60–1.53; P = 0.878). The crude 12‐month amenorrhea rate was higher among non‐obese than obese women (24.3% vs 17.5%); however, this difference was not significant after adjusting for known predictors of amenorrhea. The odds ratio was 1.28 (95% CI, 0.75–2.19; P = 0.366). Adverse events were rare and comparable between the cohorts. Conclusion: The use of EA is a safe and effective option for women with obesity.